Differentiating care for persons with mild intellectual disability or borderline intellectual functioning: a Delphi study on the opinions of primary and professional caregivers and scientists - Nouwens, Peter J. G. (BMC Psychiatry, 2020)
BACKGROUND: The demand for support for persons with mild intellectual disability or borderline intellectual functioning is growing rapidly. These persons often encounter individual and familial limitations that influence their human functioning, and often have difficulty coping with the demands of modern society. Although in the areas of policy, research and practice, people with mild intellectual disability or borderline intellectual functioning are generally approached as one group, important differences between them have been reported. Current support seems to be both suboptimal and insufficiently differentiated. METHODS: In this Delphi study we aimed to explore the need for appropriate and differentiated support for individuals with mild intellectual disability or borderline intellectual functioning. The study was based on five unique profiles of persons with mild intellectual disability or borderline intellectual functioning that are associated with individual and environmental variables. The opinions of expert primary caregivers, professional caregivers and scientists were analysed for potentially appropriate types of support for each of the five profiles. RESULTS: A total of 174 statements, divided over the five profiles, were presented to the participants. For 74 statements, consensus was reached between the expert groups. For each profile, these consensual statements represented specific items (e.g. concrete personal goals) and non-specific items (e.g. the attitude towards persons with mild intellectual disability or borderline intellectual functioning, and the coordination of health care) related to the support needs. CONCLUSION: This Delphi-based study generated consensual opinions contributing to a more differentiated system of support for individuals with mild intellectual disability or borderline intellectual functioning. Although these findings need additional investigation, they address actions that might enhance the support programmes for these individuals into more personalized support.